MECHANISMS BY WHICH BIOACTIVE COMPOUNDS OF ZUCCHINI (CUCURBITA PEPO) AND PATISSON (CUCURBITACINS AND TERPENOIDS) LIMIT CANCER CELL GROWTH AND METASTASIS THROUGH NF-κB–STAT3 SIGNALING PATHWAYS (International journal of medical sciences, 2025)
This article analyzes the chemical composition of Cucurbita pepo (zucchini) and its multivalent molecular mechanisms of anticancer activity. Phytochemical studies have shown that zucchini contains cucurbitacins, terpenoids, flavonoids, carotenoids, phytosterols, and immunomodulatory polysaccharides. These bioactive compounds suppress key oncogenic signaling axes such as NF-κB and STAT3, thereby limiting proliferation, invasion, and metastasis in cancer cells. Additionally, components of zucchini reduce the expression of MMP-2/9, VEGF, and COX-2, activate apoptotic pathways, diminish oxidative stress, and enhance immune responses within the tumor microenvironment. The findings allow the evaluation of zucchini as a low-toxic, highly bioactive, and promising nutraceutical source that may be used for cancer prevention and adjunctive therapy.